Salivary cortisol to assess the hypothalamic-pituItary-adrenal axis in healthy children under 3 years old - Silva, Margarete L. [UNESP]; Mallozi, Marcia C.; Ferrari, Giesela Fleischer [UNESP] (Sociedade Brasileira de Pediatria, 2007)
Objective: To establish reference concentration intervals for salivary cortisol in healthy children, in the morning and in the afternoon, investigating factors that interfere with the concentration measured and the possibility that circadian rhythms are present.Methods: A controlled observational study was carried out with 91 children aged 45 days to 36 months, selected at random and living in Santo Andre, state of São Paulo, Brazil. Inclusion criteria were: healthy, well-nourished, free from fever and corticoid use, subdivided by age group (five subsets) at 6-month intervals. Saliva was collected during home visits in the morning and afternoon. Cortisol was radioimmunoassayed with cortisol 3-oxime-bovine albumin antiserum.Results: the five subsets exhibited higher cortisol concentration during the morning than in the afternoon (p < 0.001), and this difference passed 30% from 1 year of age onwards. Mean concentrations, in nmol/L, were 557.86 (morning) and 346.36 (afternoon). A negative linear correlation was observed between morning concentrations and hours' sleep and frequency of meals (p < 0,05), and in the afternoon with anthropometric measurements (p < 0.05).Conclusions: Reference values for normal salivary cortisol in healthy children were established. At:45 days it was possible to observe circadian rhythms, which reached maturity at 12 months of life. Sleep and food deprivation increased morning cortisol levels.